Fabrication of fucoxanthin-loaded microsphere (F-LM) by two steps double-emulsion solvent evaporation method and characterization of fucoxanthin before and after microencapsulation - Noviendri D.; Jaswir I.; Taher M.; Mohamed F.; Salleh H.M.; Noorbatcha I.A.; Octavianti F.; Lestari W.; Hendri R.; Ahmad H.; Miyashita K.; Abdullah A. (Japan Oil Chemists Society, 2024)
Indexed by SCOPUS/WOS